High-speed advanced sensors for bioterror weapons. - Kline, C.R., Jr.
"Biological weapons" include bacteria, viruses, and toxins that are spread deliberately in air, food, or water to cause disease or death to humans, animals, or plants. This discourse addresses specifically the applicability of integrated sensors and the use of technologies (both information technologies and biological/pharmaceutical technologies) in a concerted threat identification and avoidance paradigm designed to alert, to muster, and to deploy assets in counterterrorist efforts, specifically: Do we work to identify threats far enough in advance to allow proper response? What more needs to be done? What is the worth (value) of we can do now; what do we hope to do in the future?.
Keywords: Air; Animals; Bacteria; Biological technologies; Biological weapons; Bioterror weapons; Counterterrorist efforts; Death; Disease; Food; High-speed advanced sensors; Humans; Information technologies; Integrated sensors; Pharmaceutical technologies; Plants; Threat avoidance; Threat identification; Toxins; Viruses; Water